Drone-based water sampling and characterization of three freshwater harmful algal blooms in the United States - Hanlon, Regina; Jacquemin, Stephen J.; Birbeck, Johnna A.; Westrick, Judy A.; Harb, Charbel; Gruszewski, Hope; Ault, Andrew P.; Scott, Durelle; Foroutan, Hosein; Ross, Shane D.; González-Rocha, Javier; Powers, Craig; et al. (Frontiers in Remote Sensing, 2022)
Freshwater harmful algal blooms (HABs), caused mostly by toxic cyanobacteria, produce a range of cyanotoxins that threaten the health of humans and domestic animals. Little is known about the distribution and spread of freshwater HABs. Current sampling protocols in some lakes involve teams of researchers that collect samples by hand from a boat and/or from the shoreline. These collections are often restricted to certain months of the year, and generally are only performed at a limited number of collection sites. We used a unique DrOne Water Sampling SystEm (DOWSE) to collect water samples from the surface of three different HABs in Ohio (Grand Lake St Marys, GLSM and Lake Erie) and Virginia (Lake Anna), USA in 2019. The DOWSE consisted of 3D-printed sampling device tethered to a drone (uncrewed aerial system, or UAS), and was used to collect surface water samples at different distances (10 to 100m) from the shore and from an anchored boat. One hundred and eighty water samples (40 at GLSM, 20 at Lake Erie, and 120 at Lake Anna) were collected and analyzed from 18 drone sampling missions. Mean concentrations of microcystins in drone water samples were 15.00, 1.92, and 0.02 ppb for GLSM, Lake Erie, and Lake Anna, respectively. Lake Anna had low levels of anatoxin in nearly all (111/120) of the drone water samples. Mean concentrations of phycocyanin in drone water samples were 687, 38, and 62 ppb for GLSM, Lake Erie, and Lake Anna, respectively. High levels of total phosphorus were observed in the drone water samples from GLSM (mean of 0.34 mg/L) and Lake Erie (mean of 0.12 mg/L). Lake Anna had the highest variability of total phosphorus with concentrations that ranged from 0.01 mg/L to 0.21 mg/L, with a mean of 0.06 mg/L. Nitrate levels varied greatly across sites, inverse with bloom biomass, ranging from below detection to 3.64 mg/L, with highest mean values in Lake Erie followed by GLSM and Lake Anna, respectively. Collectively, our results highlight numerous opportunities for drone-based water sampling technologies to track, predict, and mitigate HABs in the future.